2011
DOI: 10.1002/jor.21565
|View full text |Cite
|
Sign up to set email alerts
|

Subsynovial connective tissue is sensitive to surgical interventions in a rabbit model of carpal tunnel syndrome

Abstract: The most common histological finding in carpal tunnel syndrome (CTS) is non-inflammatory fibrosis and thickening of the subsynovial connective tissue (SSCT) in the tunnel. While the cause of SSCT fibrosis and the relationship of SSCT fibrosis and CTS are unknown, one hypothesis is that SSCT injury causes fibrosis, and that the fibrosis then leads to CTS. We investigated the sensitivity of the SSCT to injuries. Two types of surgical intervention were performed in a rabbit model: a skin incision with tendon lace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The mechanism underlying fibrosis involves the expression of collagen types I and III as a result of the up‐regulation of TGF‐β and CTGF expression by fibroblasts in the SSCT (Chikenji et al, ). Repeated minor trauma to the SSCT is believed to result in the up‐regulation of TGF‐β expression in fibroblasts in patients with idiopathic CTS (Sun et al, ). However, as it also occurs in individuals who do not overuse their hands, it may have other underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying fibrosis involves the expression of collagen types I and III as a result of the up‐regulation of TGF‐β and CTGF expression by fibroblasts in the SSCT (Chikenji et al, ). Repeated minor trauma to the SSCT is believed to result in the up‐regulation of TGF‐β expression in fibroblasts in patients with idiopathic CTS (Sun et al, ). However, as it also occurs in individuals who do not overuse their hands, it may have other underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies that focused on pathological changes in the median nerve used balloons or other devices to elevate pressure in the carpal tunnel, causing acute and direct pressure effects. 9,25,26 More recent studies have proposed, however, that the noninflammatory fibrotic change and thickening of the SSCT is the initiating cause of the pressure elevation, and hence of the neuropathy in idiopathic CTS. 5,6,12 In a rabbit model, two injections of 10% dextrose 1 week apart induced fibrosis in the SSCT with 6 weeks, which persisted for up to 24 weeks 12-14 as well as producing, at 12 weeks, changes in nerve physiology consistent with findings in CTS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐inflammatory synovial fibrosis is commonly observed in idiopathic CTS . Since fibrosis appears to play an important role in the pathology of this disease, we sought to characterize the fibrosis in CTS and to identify potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that even small increases in TGF‐β expression can have profound effects in the local environment and changes in receptors or second messengers such as SMAD3 can amplify the TGF‐β associated responsiveness . Given that TGF‐β is a common mediator of fibrosis in tissue and organ systems and that significant increases are found in both TGF‐β 1 and TGF‐β receptors in SSCT of CTS patients, we chose to focus on this pathway as a potential regulator and therapeutic target …”
Section: Discussionmentioning
confidence: 99%